2023
DOI: 10.1111/1753-0407.13340
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiovascular risk factors among children and young adults with type 1 diabetes during the COVID‐19 pandemic compared to previous years—Results from the German DPV registry

Abstract: Background The diverse stages of the COVID‐19 pandemic led to several social circumstances that influenced daily life and health behavior. Purpose To evaluate changes in cardiovascular risk factors and physical activity among children and young adults with type 1 diabetes (T1D) during the COVID‐19 pandemic in Germany compared to previous years. Methods A total of 32 785 individuals aged 6–21 years at baseline with T1D from the German diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…However, changes in BMI-Z-scores and physical activity in children, adolescents and young adults with type 1 diabetes documented in the DPV Registry have been investigated in two recent studies. The findings showed a reduction in physical activity but no acceleration of BMI-Z-scores among young people (6-21 years) ( 30 ), or at most a slight acceleration of BMI-Z-scores in prepubertal children only ( 31 ). We believe that adjusting for these possible confounders is unlikely to affect our results seriously.…”
Section: Discussionmentioning
confidence: 91%
“…However, changes in BMI-Z-scores and physical activity in children, adolescents and young adults with type 1 diabetes documented in the DPV Registry have been investigated in two recent studies. The findings showed a reduction in physical activity but no acceleration of BMI-Z-scores among young people (6-21 years) ( 30 ), or at most a slight acceleration of BMI-Z-scores in prepubertal children only ( 31 ). We believe that adjusting for these possible confounders is unlikely to affect our results seriously.…”
Section: Discussionmentioning
confidence: 91%
“…An increased in BMI, increase in screen time, reduction in physical activity was reported among children/ adolescents with diabetes in many studies (see Table 1 ). Further, a large-scale study among children and adolescents with type 1 diabetes in Germany showed increase in prevalence of cardiovascular risk factors during the lockdown period, such as rise in blood pressure level and atherogenic lipid levels [45] .…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
“…We found 33 studies that looked at the effects of COVID-19 on diabetes among children/adolescents ( Table 1 [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24*] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38*] , [39] , [40] , [41] , [42] , [43] , [44] , [45*] , [46] , [47*] ), of which most focused only on those with TID. One study included both T1D and T2D [46] and one T2D [47] ( Table 1 ).…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
“…Additionally, the ratio of TC/HDL and LDL/HDL was calculated. HbA1c values were standardized to the Diabetes Control and Complications Trial reference range of 4.05%–6.05% (20.7–42.6 mmol/mol) using the multiple of the mean transformation method to account for different laboratory methods 15,16 . Hypertension was defined as systolic blood pressure (BP) ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg.…”
Section: Methodsmentioning
confidence: 99%
“…HbA1c values were standardized to the Diabetes Control and Complications Trial reference range of 4.05%–6.05% (20.7–42.6 mmol/mol) using the multiple of the mean transformation method to account for different laboratory methods. 15 , 16 Hypertension was defined as systolic blood pressure (BP) ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg. Metabolic syndrome was defined per the International Diabetes Federation Consensus Statement 17 as obesity (BMI ≥30 kg/m 2 , because waist circumference was not available in most individuals) and one of the following: TG >150 mg/dL, HDL <40 mg/dL (males) or <50 mg/dL (females), lipid‐lowering medication, systolic BP ≥130 mm Hg or diastolic BP ≥85 mm Hg, or antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%